Entrepreneurial Marketing for Small and Medium Enterprises (SMEs) Business: An Exploratory Study on Entrepreneurial Performance - Mayasari, Iin; Wiadi, Iyus; Maharani, Anita (International Research Journal of Business Studies, 2009)
This study is an exploratory study that aims at applying entrepreneurial marketing concepts to identify and understand abilities of small and medium scale businesses to gain performance. Entrepreneurial marketing includes activities to develop and exploit social capital. Entrepreneur performance can be measured by both objective and subjective perspective. Objective perspective is measured using quantitative measurement while subjective perspective is measured by the entrepreneur’s perception on his/her ability to manage the business. Qualitative methodology used in this research was done by interviewing small and medium scale business entrepreneurs.